An Epidemiological Study on Association Between Alcohol and Tobacco Use in An Urban Slum of Meerut - Katyal, Rashmi; Bansal, Rahul; Goel, Kapil; Sharma, Sachin (National Journal of Community Medicine, 2013)
Introduction: Alcohol consumption and problems related to alcohol vary widely around the world, but the burden of disease and death remains significant in most countries. Though there are studies indicating co-occurrence of alcohol use with tobacco, not much work is done on association of alcohol and tobacco use in India. Methods: A cross-sectional study was conducted in the catchment area of UHTC (Urban Health and training Centre) among 324 males aged > 15 years. Data was collected by home visit using WHO questionnaire (AUDIT: Alcohol use disorder identification test) Modified Kuppuswamy scale was used to assess the socio-economic status of the families. Also, data was collected to know the association of alcohol use with tobacco. Data was analyzed by chisquare test using SPSS 20.0 version. Results: Among current drinkers, 56.2% used smoked tobacco while 11.8% of the teetotallers were smokers. Similarly, smokeless tobacco was used by 48.9% of current drinkers and 2.6% of the teetotallers. A highly statistically significant association was found between tobacco use and alcohol use (p value<0.001). Conclusions: It can be very well concluded that alcohol users are more indulged into tobacco use as compared to teetotalers. Therefore, high risk screening for tobacco use among the alcoholics can be a vital step in the prevention of addiction, which is emerging as one of the major risk factor for non-communicable diseases.